Management of ginger bacterial wilt (Ralstonia solanacearum) epidemics by biofumigation at Tepi, southwestern Ethiopia - Jibat, Merga; Alo, Shamil (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2022)
Bacterial wilt of ginger, caused by Ralstonia solanacearum, is the most damaging disease, which brings rapid and serious wilting, and reduces the quality and yield of ginger rhizome in Ethiopia. Thus, an experiment was carried out to evaluate the effect of different biofumigants on bacterial wilt in Ethiopia during the 2019 and 2020 main cropping seasons. The experiments were conducted at the Tepi Agricultural Research Center. Different biofumigation soil amendments (citronella, palmarosa, mint, lemongrass and Chinese chive) were applied before planting. The trials were arranged in a randomized complete block design with three replications. Examination of variance showed that soil amendments with biofumigants strongly decreased bacterial wilt severity and improved rhizome yield and components. Rhizome yield gains of about 90.2% were achieved by soil biofumigation with lemongrass, as compared to untreated control. The relative mean rhizome yield damage due to bacterial wilt in the control plot was 47.4%. Wilt severity was inversely and very significantly (p <0.01) proportional (r = -0.90**) to rhizome yield. The overall results of the study show that soil amendments with botanicals, particularly lemongrass, before planting should be used to manage ginger bacterial wilt in experimental areas and further similar agro-ecologies.